ANTIBODY GENERATION FOR DETECTION OF PHOSPHOGLYCEROYL PROTEIN ADDUCTS - Shatkenova, Zariat (Nazarbayev University School of Sciences and Humanities, 2024)
One of the reactions of glycolysis, which is controlled by the enzyme GAPDH, results in the synthesis of 1,3- bisphosphoglycerate. A highly reactive intermediate product known as cyclic 1,3-phosphoglycerate (cPGA) can be formed from 1,3-bisphosphoglycerate. In previous studies, it was shown that the knock-out of PARK7/DJ1 can cause an accumulation of highly reactive cPGA and its adducts. However, the quantifiable methods to detect cPGA adducts were lacking. We created a novel technique for the detection of cPGA modifications with antibodies specifically recognizing cPGA-modified lysine and cysteine residues. We developed a procedure for the generation of antigens modified by cPGA. We produced antibodies that recognize lysine and cysteine residues modified by cPGA. Finally, we purified these antibodies by negative selection with the help of affinity chromatography. Our results demonstrated that purified antibodies can specifically recognise a diverse range of cPGA-modified proteins and can be used for Western Blot analysis of cell extracts.
Keywords: cPGA; phospho-glyceroyl protein adducts; DJ 1; GAPDH; Type of access: Restricted